Peningkatan Hasil Belajar Siswa Dengan Metode Card Sort Tentang Siklus Hidup Makhluk Hidup - Muslimin Muslimin; Muspratiwi Pertiwi MR; Jumaini Jumaini (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to improve the process and student learning outcomes by applying the card sort learning method about the life cycle.  This study uses a qualitative approach with the type of classroom action research (CAR).  The research sample is 20 students whose learning outcomes have not reached the minimum learning completeness standard (SKBM). Data collection techniques in this study used observation, test and documentation techniques.  The data analysis technique consists of four activities, namely data condensation, data presentation, data verification and drawing conclusions.  The results of the study indicate that through the application of the card sort learning method it is proven to be able to improve the process and student learning outcomes.